Water budgeting in a carp-prawn polyculture system: impacts on production performance, water productivity and sediment stack - Mohanty, R.K.; Mishra, Atmaram; Panda, D.K.; Patil, D.U. (Hindawi Limited, 2016)
This study was designed to quantify the total water requirement and consumptive water use in carpprawn polyculture system under different water management protocols, using water balance model. Under different water management protocols, treatment-wise estimated total water use, TWU (9104, m3) was 3.7, 4.6 and 3.9, while the computed consumptive water use index, CWUI (m3 kg 1 biomass) was 6.62, 9.31 and 7.08, in T1 (no water exchange), T2 (periodic water exchange) and T3 (regulated water exchange) respectively. Significantly higher yield (P < 0.05) in both T2 and T3 over T1, was probably due to water exchange that improved the rearing environment. Although intensity of water exchange was more in T2, significant variation (P < 0.05) in overall growth and yield was not recorded between T2 and T3. Treatmentwise sediment load ranged between 54.6 and 71.3 m3 t 1 biomasses. Higher sediment load was recorded at lower intensity of water exchange as well as with higher apparent feed conversion ratio. Higher net total water productivity, net consumptive water productivity and OV-CC ratio in T3 infers that regulated water exchange has a distinct edge over the no water exchange protocol. Restricted water use instead of regular/excess water exchange not only improves the production performance and water productivity, but also helps in lessening the operational pumping cost.